Hearing Difficulties as a Result of Traumatic Brain Injury. - Roup, Christina M.; Ross, Courtney; Whitelaw, Gail (Journal of the American Academy of Audiology, 2020)
Background: Traumatic brain injury (TBI) has been shown to result in hearing difficulties (i.e., deficits in the processing of auditory information) without impacting pure-tone threshold detection. A missed diagnosis of hearing difficulties due to TBI because of normal hearing can lead to reductions in quality of life and missed opportunities to provide an appropriate treatment regimen. Purpose: This study presents a case report of a female patient with a history of TBI due to a motor vehicle accident that resulted in a broad range of symptoms, including self-perceived hearing difficulties and poorer-than-normal auditory processing performance. Research Design: Case report. Study Sample: A 58-year-old woman with a history of a mild TBI due to a motor vehicle accident. Data Collection: A neuro-audiology evaluation was conducted to address the patient's hearing complaints. The evaluation included standard audiometric and auditory processing test batteries. Results: The case report focuses on the patient's history of TBI and her presentation to our clinic with hearing complaints. Her clinical audiological outcomes, including an auditory processing assessment, and treatment with mild-gain hearing aids are discussed. The use of mild-gain hearing aids resulted in improved auditory processing skills and a significant improvement in quality of life. Conclusions: Patients with a history of TBI often have multiple and debilitating symptoms, including hearing difficulties. Accurate diagnosis of auditory processing deficits in the face of normal pure-tone detection abilities is essential to provide treatment options that can improve daily function and quality of life.